Austrian corporatism and institutional change in the relationship between apprenticeship training and school-based VET - Graf, Lukas [Verfasser]; Lassnigg, Lorenz [Verfasser]; Powell, Justin J. W. [Verfasser] (My University, 2012)
"Austria's vocational education and training (VET) system displays a unique structure that joins a strong dual apprenticeship system with a robust full-time school-based VET. This school-based trajectory has deep historical roots and has considerably influenced recent reforms in apprenticeship. Current dynamics in the Austrian skill formation system are explained here by a historical-institutionalist account, which focuses on the power relationship between the state, trade unions, and employers. However, we also find differences within the employers' camp, depending on firm size. The particular mix of school-based and apprenticeship pathways in the Austrian VET system is strongly influenced by small-state corporatism; yet, this influence is challenged by the rise of state-provided, school-based VET. Further crucial factors impacting the evolution of apprenticeship are centralized federalism, privatization of large firms, and accession to the European Union. Applying the method of process tracing, we identify 'layering' and 'drift' as the dominant modes of institutional change in Austria's VET system." (Autorenreferat, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Historische Entwicklung; Duales System; Modularisierung; Schulische Berufsausbildung; Hochschulbildung; Österreich